STUDI LITERATUR TENTANG PENGGUNAAN RATIONAL EMOTIVE BEHAVIOR THERAPY UNTUK KALANGAN REMAJA - Andhyni B, Putry; Umari, Tri; Saam, Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study was conducted to determine the basic concepts and theories, implementation techniques REBT and types of adolescent problems using Rational Emotive Behavior Therapy (REBT). The type of research used is literature study. The instrument used in this research is a combination of national and international journals. Data analysis in this study used qualitative. The results showed that Rational Emotive Behavior Therapy (REBT) the type of counseling approach that focuses on aspects of thinking, assesing, and deciding with the aim of helping individuals to think more rationally. And there are also various theories found in the research results from the research results that can be used as discussing one of the problem formulations of the results of the research. As for the use of Rational Emotive Behavior Therapy (REBT) was widely used among teenagers. And there are also several technical models of implementing the Rational Emotive Behavior Therapy (REBT) approach such as through group counseling formats, group guidance, individual counseling, and combining cognitive, imagery and behavioristic techniques. The types of adolescent problems that use rational emotive therapy are internal and external problems for adolescents.Key Words: Literature study, Rational Emotive Behavior Therapy, adolescents